Integral-Universal Education: Analysis of M. Natsir’s Thoughts on Islamic Education - Kasmuri Selamat (Institut Agama Islam Negeri (IAIN) Curup, 2020)
This paper aimed at exploring M. Natsir's thoughts on Islamic education. Using a qualitative study with a historical approach, the writer found that M. Natsir was a rare figure. He was not only a scholar but also a thinker, a politician, and an educator. As an educator, he not only became a teacher, but also gave birth to various educational concepts known as an integral and universal education concept. He was an architect and an anti-dichotomous thinker of Islamic education. According to Natsir, Islam did not separate spiritual matters from worldly affairs. The spiritual aspect would be the basis of worldliness. The foregoing indicated that religious ethics emphasized by Islamic teachings must be the foundation of life. The conceptual basis of